2015
DOI: 10.1080/09168451.2014.978258
|View full text |Cite
|
Sign up to set email alerts
|

Both HMG boxes in Hmo1 are essential for DNA binding in vitro and in vivo

Abstract: Hmo1, a member of the high mobility group B family proteins in Saccharomyces cerevisiae, associates with the promoters of ribosomal protein genes (RPGs) to direct accurate transcriptional initiation. Here, to identify factors involved in the binding of Hmo1 to its targets and the mechanism of Hmo1-dependent transcriptional initiation, we developed a novel reporter system using the promoter of the RPG RPS5. A genetic screen did not identify any factors that influence Hmo1 binding, but did identify a number of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Based on this result, we proposed that box A, in addition to box B, is essential for DNA‐binding activity of Hmo1 (Higashino et al . ). However, another previous study carried out by others suggested that although box B is responsible for most of the DNA‐binding activity of Hmo1, box A has only a slight, if any, influence on DNA binding (Kamau et al .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Based on this result, we proposed that box A, in addition to box B, is essential for DNA‐binding activity of Hmo1 (Higashino et al . ). However, another previous study carried out by others suggested that although box B is responsible for most of the DNA‐binding activity of Hmo1, box A has only a slight, if any, influence on DNA binding (Kamau et al .…”
Section: Resultsmentioning
confidence: 97%
“…For this purpose, we conducted the TSS (Transcription Start Site) shift assay, using a reporter plasmid consisting of the modified RPS5 promoter and HIS3 gene, developed in our previous study to test the DNA binding of Hmo1 in vivo (Higashino et al . ). Hmo1 binds to the intervening region between the UAS and core promoter in the modified RPS5 promoter, thereby inhibiting transcriptional initiation of ectopic mRNAs that can produce functional His3 protein.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations